Perlindungan Hukum dan Upaya Pencegahan Pencabulan Anak di Indonesia - Nur Amalia Zahra (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Child molestation remains a serious issue in Indonesia, requiring strong legal protection and effective prevention efforts. This study aims to analyze the legal framework for child protection, the implementation of legal protection for victims, prevention efforts, and challenges in law enforcement related to child molestation in Indonesia. Using a literature review method, this research examines various current literature sources. The results show that although Indonesia has a comprehensive legal framework, its implementation still faces challenges such as child-unfriendly judicial processes and limited resources. Prevention efforts involve comprehensive sexual education and active community participation. This study recommends strengthening legal sanctions, improving law enforcement capacity, developing child-friendly justice systems, and intensifying community education programs to enhance protection and prevention of child molestation in Indonesia.